Building a mentally healthy generation: Stress management approaches for students at SMPN 13 Surakarta - Syifa', Farichah Nurus; Indratama, Inmas; Sholikhah, Tri Pujiati; Japar, Muhammad (Universitas Muhammadiyah Magelang, 2025)
Adolescents who experience stress and are unable to cope with it are at risk of experiencing various negative impacts. Therefore, the development of a stress management program is essential. The purpose of this community service is to enhance students' understanding of stress and its management techniques, enabling them to manage stress more effectively. The method used in this service consists of three stages: preparation, implementation, and evaluation. This activity includes socialization on stress, stress management, and the use of journaling as a stress reduction medium. The results of this activity include the identification of stress-causing factors, such as traumatic experiences, pressure from others, family problems, unhealthy situations, and so on. Nevertheless, several positive impacts were observed after the activity, such as increased knowledge about stress and appropriate ways to manage it.